Photobacterium damselae subsp. damselae, a bacterium pathogenic for marine animals and humans - Rivas, Amable J.; Lemos, Manuel L.; Osorio, Carlos R. (Frontiers in Microbiology, 2013)
Photobacterium damselae subsp. damselae (formerly Vibrio damsela) is a pathogen of a variety of marine animals including fish, crustaceans, molluscs and cetaceans. In humans, it can cause opportunistic infections that may evolve into necrotizing fasciitis with fatal outcome. Although the genetic basis of virulence in this bacterium is not completely elucidated, recent findings demonstrate that the phospholipase-D Dly (damselysin) and the pore-forming toxins HlyApl and HlyAch play a main role in virulence for homeotherms and poikilotherms. The acquisition of the virulence plasmid pPHDD1 that encodes Dly and HlyApl has likely constituted a main driving force in the evolution of a highly hemolytic lineage within the subspecies. Interestingly, strains that naturally lack pPHDD1 show a strong pathogenic potential for a variety of fish species, indicating the existence of yet uncharacterized virulence factors. Future and deep analysis of the complete genome sequence of P. damselae subsp. damselae will surely provide a clearer picture of the virulence factors employed by this bacterium to cause disease in such a varied range of hosts.